BIOCHAR-SUPPLEMENTED IN VITRO CULTURE OF MUSA ACUMINATA VAR. BARANGAN TO CONTROL CONTAMINATION AND ENHANCE REGENERATION - Tuwo, Mustika; Fahruddin; Tambaru, Elis; Syam , Nabila; Fadilah, Nur; Jaga, S. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
This study aimed to evaluate the effectiveness of coconut shell-derived biochar supplementation in Murashige and Skoog (MS) medium to suppress contamination and enhance regeneration efficiency. A Completely Randomized Design (CRD) with 11 biochar concentrations (0–5 g/L) was used, each with three replicates. Parameters observed included contamination and browning onset, browning intensity, propagule formation time, fresh weight, shoot number, and shoot height. Results showed that biochar significantly delayed contamination and browning. The 2 g/L treatment yielded the best results: 13.8 days after culture (DAC) for contamination and 12.67 DAC for browning. The lowest browning intensity (score 1.41) occurred at 5 g/L. Propagule formation was fastest at 3 g/L, while optimal shoot multiplication and height were observed at 2 g/L. These benefits are attributed to biochar’s ability to enhance nutrient availability, adsorb phenolics, stabilize pH, and regulate endogenous hormones. However, concentrations ≥4 g/L reduced culture performance, likely due to osmotic stress and media imbalance.